(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Abstract: In India, eco-friendly food products are in the developing stage, which were encouraged and supported by the government and various other private initiatives. The consumers are also changing drastically towards consuming eco-friendly food products because most of the consumers want to maintain their health and they try to avoid various diseases caused by eco-friendly food. The main objective of the study is to explore the influence of consumers’s psychological factors and demographic factors on the buying behavior of consumers towards the usage of eco-friendly food products. A research study was conducted in Mysore and Chamarajanagara districts, selecting a sample of 788 eco-friendly food product consumers. A structured questionnaire was prepared containing the Likert-scaling technique applied to measure the satisfaction level of customers on various quality aspects of eco-friendly food products. The research design is both descriptive and analytical. The purposive sampling technique was used to collect the primary data, and regression analysis was used as a statistical tool. It is found that the unique contribution of the variables of consumer’s psychographic factors, such as the presence of children within the household, followed by the attractiveness of green products, health consciousness, naturally grown food, innovation in the agro-food system, increased consumer’s interest, helping farmers indirectly, and eco-friendly product packaging, has a significant influence on the buying behavior of consumers towards usage of eco-friendly food products. The unique contribution of the variables of the consumer’s demographic factors, such as age, followed by gender, work experience, family size, marital status, no. of children in the family, occupation, stage of life cycle, social status, and customer location, has a significant influence on the buying behavior of consumers towards the usage of eco-friendly food products.